2014
DOI: 10.1007/s11060-014-1552-9
|View full text |Cite
|
Sign up to set email alerts
|

MRI-guided 3D conformal arc micro-irradiation of a F98 glioblastoma rat model using the Small Animal Radiation Research Platform (SARRP)

Abstract: Current glioblastoma (GB) small animal models for cranial radiation therapy (RT) use simple single beam technologies, which differ from the advanced conformal image-guided radiation techniques used in clinical practice. This technological disparity presents a major disadvantage for the development of new therapeutic approaches. Hence, we established a F98 GB rat model using magnetic resonance imaging (MRI)-guided three-dimensional (3D)-conformal arc RT with the Small Animal Radiation Research Platform (SARRP).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 18 publications
2
34
0
Order By: Relevance
“…On the day of PET imaging, the mean contrast enhancing tumor volume on T1-weighted MRI was 99 ± 73 mm 3 (n = 16). GB histology was confirmed (Fig 1D) [9,23]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the day of PET imaging, the mean contrast enhancing tumor volume on T1-weighted MRI was 99 ± 73 mm 3 (n = 16). GB histology was confirmed (Fig 1D) [9,23]. …”
Section: Resultsmentioning
confidence: 99%
“…Conformal arc micro-irradiation was optimized previously [23]. 3 arcs and a 3x3 mm collimator were used for the delivery of 60 Gy in a single dose (Fig 1E).…”
Section: Methodsmentioning
confidence: 99%
“…Although physical separation of the abdominal structures was achieved, the accuracy of dose estimation remained limited [6]. Other imaging modalities such as Positron Emission Tomography (PET) and Bioluminescence imaging (BLI) also have been proposed to guide targeting and delivery of radiotherapy [2, 911] but both techniques have their inherent limitations. BLI is restricted by its light penetration depth, lack of true tomography imaging and requires the use of reporter genes whilst PET applications are also limited by partial volume effects and in some cases, inadequate contrast specificity.…”
Section: Introductionmentioning
confidence: 99%
“…However, MRI has to date been used merely as a descriptor of target location [2, 12] in studies involving organs other than the brain. MRI-guided radiotherapy (RT) has only focussed on brain, an organ that is easy to immobilise with internal, fixed landmarks [2, 9, 11, 12]. As such, the skull’s bright intensity on CT but dark intensity on MRI was used to drive a rigid body registration.…”
Section: Introductionmentioning
confidence: 99%
“…Advanced beam delivery including non-coplanar treatment fields and arc therapy. [6] Prior studies have demonstrated the efficacy of radiation administered using the SARRP to intracranial tumors. [5,7,8] However, the question remains whether the treatment is precise and the dose is accurate.…”
Section: Introductionmentioning
confidence: 99%